Antibacterial bibenzyl derivatives from the tubers of Bletilla striata. (June 2019) - Jiang, Sai; Wan, Ke; Lou, Hua-Yong; Yi, Ping; Zhang, Ni; Zhou, Mei; Song, Zhi-Qin; Wang, Wei; Wu, Ming-Kai; Pan, Wei-Dong
Abstract: Ten previously undescribed bibenzyl derivatives (bletistrins A-J), including 5 that have hydroxyl-substituted chiral centres on the aliphatic bibenzyl bridge, along with twelve known bibenzyl derivatives, were isolated from the rhizomes of Bletilla striata . The structures of bletistrins A-J were primarily elucidated on the basis of their 1D and 2D NMR spectroscopic data. The absolute configurations of bletistrins A, D, F, H and I were determined by electronic circular dichroism (ECD) spectroscopic analysis and optical rotation value. Most of the isolated compounds were evaluated for their antibacterial activities against 3 g-positive bacterial strains and 1 g-negative bacterial strain. Bletistrins F, G, and J, bulbocol, shanciguol and shancigusin B showed inhibitory activities, with MICs of (3–28  μ g/mL) against S . aureus ATCC 6538. Graphical abstract: Image 1024 Highlights: Ten undescribed bibenzyls were isolated from Bletilla striata. Five bibenzyls possess hydroxyl-substituted chiral centres on the aliphatic bibenyl bridge. Most of the bibenzyls showed a range of inhibitory activities against S. aureus ATCC 6538 with MICs of 3–28  μ g/mL.